Ethics and Theological Significance of Animal Slaughter in Islam: A Critical Literature Review - Fikal; Saddam Firmansyah; Agung Pranoto Kadiatmaja (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2026)
This study aims to critically examine the ethics and theological significance of animal slaughter in Islam through a library research approach. The study is motivated by the growing tendency of legalistic reductionism in both academic discourse and industrial practice, where formal compliance is prioritized over ethical and spiritual dimensions. By employing qualitative analysis of primary sources such as the Al-Qur'an, Prophetic traditions (hadith), as well as classical works of tafsir and fiqh, and supported by contemporary literature, this research seeks to reconstruct an integrative framework of Islamic slaughter. The findings reveal that animal slaughter in Islam encompasses three fundamental dimensions: theological (tawhid), ethical (ihsan), and legal-practical (fiqh regulations). However, in modern industrial contexts, these dimensions are often fragmented, resulting in a gap between formal halal certification and ethical quality (tayyib). This study argues that slaughter cannot be reduced to a mere technical procedure but must be understood as an act of worship that reflects obedience to God and moral responsibility toward living beings. Therefore, a paradigm shift from legal compliance to ethical compliance is necessary to ensure that halal principles align with ihsan, animal welfare standards, and global demands for sustainable food systems.